Critical theory in critical times : transforming the global political and economic order - Deutscher, Penelope, 1966-; Lafont, Cristina, 1963- (New directions in critical theory., 2017)
We live in critical times. We face a global crisis in economics and finance, a global ecological crisis, and a constant barrage of international disputes. Perhaps most dishearteningly, there seems to be little faith in our ability to address such difficult problems. However, there is also a more positive sense in which these are critical times. The world's current state of flux gives us a unique window of opportunity for shaping a new international order that will allow us to cope with current and future global crises. In Critical Theory in Critical Times, eleven of the most distinguished critical theorists offer new perspectives on recent crises and transformations of the global political and economic order. Essays from Jürgen Habermas, Seyla Benhabib, Cristina Lafont, Rainer Forst, Wendy Brown, Christoph Menke, Nancy Fraser, Rahel Jaeggi, Amy Allen, Penelope Deutscher, and Charles Mills address pressing issues including international human rights and democratic sovereignty, global neoliberalism, novel approaches to the critique of capitalism, critical theory's Eurocentric heritage, and new directions offered by critical race theory and postcolonial studies. Sharpening the conceptual tools of critical theory, the contributors to Critical Theory in Critical Times reveal new ways of expanding the diverse traditions of the Frankfurt School in response to some of the most urgent and important challenges of our times.